RELATIONSHIP MANAGEMENT IN BRAND POSITIONING: AN ASSESMENT ON WEB PAGES IN THE BANKING SECTOR - Emel Tanyeri MAZICI (Fırat University, 2019)
One of the main points of branding process in the positioning of the brands in the mind and being permanence are establishing and managing a network of relationship that can create added value to the parties. Especially, the relationship management on web pages which gains wide currency is extremely important for all corporations and sectors which have aim of branding. In this study, the relationship management on web pages is analyzed over the scale developed by Kent, Taylor and White (2001) on the basis of banking which is the leading one among the sectors, branding in Turkey and creating added value to country’s economy as well as the parties. There are 8 categories and 48 associated sub-items in the study scale. It’s observed in Turkey sample that the banks have the highest average in usefulness of information towards the investors in the category of usefulness of information and the lowest average is available in the scale items of return visit and conservation of visitors. Additionally, the results showed that the banks in Turkey sample mainly tend to be information provider in relationship management on web, for this reason it should include more interactive activities. The high frequency of certain categories and their sub-items shows that the limited number of banks progresses positively in some items while some features are widely used across the banks. This result is indicative of the importance of finding undiscovered areas and being pioneer in using these areas in brand positioning. Thus, the brand positioning in minds requires to being different and developing new applications.